Determinants of Customer Sharia Financial Management Behavior in Choosing Multiguna-Asn Financing Through Income - Santi Arafah; Yunanda Eka Putra; Iskandar Muda; Andri Soemitra; Yusrizal (Institut Agama Islam Negeri Lhokseumawe, 2025)
This research aims to determine the determinant factors that influence sharia financial management behavior through income on mutliguna ASN financing at PT Bank Sumut Syariah KCPsy Marelan. The population and sample in this research were 98 customers who were registered in Mutliguna-ASN financing. Data analysis in this study used SEM-PLS analysis techniques. The results of the research conducted with a confidence level of 95% based on sig. 5%, states that sharia financial literacy, financial experience and sharia financial attitudes affect sharia financial management behavior, while income does not affect sharia financial management behavior. Individual income greatly contributes to managing their finances due to the desire and satisfaction factors that want to be fulfilled, especially in Multiguna-ASN financing. This financing is one of the ideal solutions for middle to lower class people who face economic limitations, because it provides easier and faster access to customers to obtain the funds needed, but this financing is only intended for ASN.